Manhaj Waḥīd ad-Dīn Khān fī al-’Aqīdah wa Taṭbīquhu fī Qaḍiyyati Wujūdi Allāh: [Waḥīd ad-Dīn Khān’s Approach to Theology and Its Application in the Discourse of God’s Existence] - Bin Has, Qois Azizah; Farhah, Farhah; Sifa’urrohmah, Astuti (UIN Sunan Kalijaga Yogyakarta, 2022)
Waḥid ad-Dīn Khān has a profound interest in questions of faith within the discourse of Kalam with the emergence of challenges in religion and the cognitive explosion in contemporary thought. In this case, Khān is encouraged to defend Islamic theology from challenges, such as the evidence-based questions about the existence of God. Those inquiries are arising among Western atheists, who are seeking scientific, empirical, and rational evidence. Responding to this challenge, Khān defends the theology by introducing a fresh paradigm of Kalam, a scientific theory based on Quranic foundations. This discourse encourages the ramification of Quranic values to remind God’s intention, configures the “scientific” verses with new scientific discoveries, inspires the complete verses of God in the human soul, and integrates Islamic-theological literature with scientific methods. Khān argues that modern scientific discoveries are parallel with the Qur'an, in which the human mind and divine revelation are colliding with each other.